Modelling Shocks to New Zealand's Fiscal Position - Craig Fookes (New Zealand Government, The Treasury, 2011)
This paper explores the use of scenario analysis as a contingency planning tool to examine how various purposefully-severe shocks could impact on the Crown's fiscal position. A magnitude 7.8 earthquake and a process of domestic deleveraging are used to test the resilience of the fiscal position (respectively) to a one-off spike in spending and a more protracted downturn in the economy. A New Zealand economic crisis is not considered imminent, but historically unprecedented levels of private sector debt present a risk for the country's finances. Scenario analysis can model hypothetical shocks based on past experience either in New Zealand or abroad. However, the results cannot take into account many of the factors that allowed New Zealand to come through the recent global financial crisis in a better position than many other developed economies. The tool's usefulness is in considering how the size and structure of the balance sheet affect policy sustainability in a shock. Our results suggest that a sustained decline in tax revenue represents a key risk to the fiscal position. The adjustments necessary to continue debt repayments and avoid a liquidity crisis are compared to historic episodes of fiscal consolidation. While low government debt provides a significant buffer, the resulting (necessary) burden of adjustment in a larger crisis could still fall heavily on taxpayers through fairly rapid changes to tax or government spending.
Keywords: E65; 330; fiscal policy; risk management; Crown balance sheet; sovereign debt; Wirtschaftskrise; Finanzkrise; Katastrophe; Schock; Öffentliche Einnahmen; Internationale Staatsschulden; Neuseeland